Pemetaan pola keragaman konten perilaku perundungan daring pada remaja melalui media sosial - Murwani, Endah (Jurnal Studi Komunikasi, 2023)
The research aims to map the pattern of cyberbullying content diversity produced by adolescents through social media. The netnographic method is used to observe cyberbullying behavior in adolescent communities that are connected through social media. The research is a realist ethnography in nature, describing cyberbullying behavior from the content of youth community conversations. Research participants were adolescents aged 17-22 years who used social media and had been involved in cyberbullying, both as perpetrators and/or victims. Data was collected through participatory observation by being directly involved in the participants' social media activities. The results of the study identify cyberbullying content that is often sent by perpetrators and received by victims. First, flaming - content that contains anger, harsh words and vulgarity. Second, online harassment – ​​teasing, physically insulting and mocking parents' names. In addition, denigration was found - content created by gossiping about something that is not true; impersonation, uploading content that embarrasses the victim; and outing and trickery, sending dark jokes related to religion. The implications of this cyberbullying content mapping are for developing a literacy model for preventing cyberbullying behavior in adolescents who are easily exposed and unknowingly carry out cyberbullying behavior towards their peers.